Herpes Simplex Virus Type 2 Glycoprotein E Is Required for Efficient Virus Spread from Epithelial Cells to Neurons and for Targeting Viral Proteins from the Neuron Cell Body into Axons - Wang, Fushan (2010)
The HSV-2 lifecycle involves virus spread in a circuit from the inoculation site to dorsal root ganglia and return. We evaluated the role of gE-2 in the virus lifecycle by deleting amino acids 124–495 (gE2-del virus). In the mouse retina infection model, gE2-del virus does not spread to nuclei in the brain, indicating a defect in anterograde (pre-synaptic to post-synaptic neurons) and retrograde (post-synaptic to pre-synaptic neurons) spread. Infection of neuronal cells in vitro demonstrates that gE-2 is required for targeting viral proteins from neuron cell bodies into axons, and for efficient virus spread from epithelial cells to axons. The mouse flank model confirms that gE2-del virus is defective in spread from epithelial cells to neurons. Therefore, we defined two steps in the virus lifecycle that involve gE-2, including efficient spread from epithelial cells to axons and targeting viral components from neuron cell bodies into axons.